Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes productivity growth in Belgium. It highlights that Belgium's subdued productivity growth can be explained by a combination of sectoral employment shifts, barriers to competition, the declining quality of infrastructure, and an aging workforce. The shift of employment toward lower productivity service sectors, common to many advanced economies, has been more pronounced in Belgium and explains half of the productivity gap with neighboring countries. Population aging is another secular factor that has contributed to the productivity slowdown. In addition, barriers to competition in some service sectors have lowered productivity growth and raised rents in these sectors.